2021
DOI: 10.3389/fcell.2021.809859
|View full text |Cite
|
Sign up to set email alerts
|

Polyadenylated RNA and RNA-Binding Proteins Exhibit Unique Response to Hyperosmotic Stress

Abstract: Stress granule formation is a complex and rapidly evolving process that significantly disrupts cellular metabolism in response to a variety of cellular stressors. Recently, it has become evident that different chemical stressors lead to the formation of compositionally distinct stress granules. However, it is unclear which proteins are required for the formation of stress granules under different conditions. In addition, the effect of various stressors on polyadenylated RNA metabolism remains enigmatic. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…However, its function related to RG4 regulation and mRNA translation has not been investigated yet. In agreement with previous data reporting the function of hnRNP U in the cytoplasm [59][60][61][62][63] , we observed that, beyond its presence in nuclear fractions, hnRNP U was enriched in cytosolic and microsomal fractions (Fig. 3a).…”
Section: Hnrnp U Binds To Rg4-containing Nuclear-encoded Mitochondria...supporting
confidence: 93%
“…However, its function related to RG4 regulation and mRNA translation has not been investigated yet. In agreement with previous data reporting the function of hnRNP U in the cytoplasm [59][60][61][62][63] , we observed that, beyond its presence in nuclear fractions, hnRNP U was enriched in cytosolic and microsomal fractions (Fig. 3a).…”
Section: Hnrnp U Binds To Rg4-containing Nuclear-encoded Mitochondria...supporting
confidence: 93%